Lubricating oil composition and preparation method thereof
By introducing a combination of specific copolymers and additives into the lubricating oil, the viscosity problem of lubricating oil in wind power transmission systems under temperature difference environments is solved, achieving excellent viscosity-temperature performance and anti-wear properties, making it suitable for wind power transmission systems.
Patent Information
- Application Number
- CN202411295735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2026-03-20
AI Technical Summary
In wind power transmission systems, lubricating oil viscosity decreases at high temperatures, leading to friction and wear, while viscosity increases at low temperatures, causing solidification and affecting lubrication efficiency. It is also prone to micropitting and wear. Existing viscosity index improvers cannot simultaneously meet the requirements of high-temperature lubrication and low-temperature fluidity.
A copolymer of C8-C12 alkyl methacrylate, C13-C18 alkyl methacrylate, and N-vinylimidazole is used as a viscosity index improver. Combined with additives such as thiophenol ester antioxidants, polyisobutylene succinimide, sulfurized olefins, dialkyl dithiocarbamate, and phosphate esters, a multifunctional lubricating oil composition is formed. The viscosity index improver is prepared through copolymerization reaction to optimize lubrication performance.
It achieves excellent viscosity-temperature properties, extreme pressure anti-wear properties, and low-temperature fluidity of lubricating oil over a wide temperature range, extending the service life of wind power transmission systems and reducing fuel consumption and wear.
Smart Images

Figure BDA0005045989930000061 
Figure BDA0005045989930000101 
Figure BDA0005045989930000111
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a lubricating oil composition, in particular to a lubricating oil composition suitable for wind power transmission system and a preparation method thereof. BACKGROUND
[0002] The implementation of various low-carbon environmental protection regulations promotes the continuous growth of renewable energy. Wind power, as a clean and sustainable energy, is rapidly rising and widely used around the world. Wind power plants in China are mostly concentrated in the severely cold northeast, northwest and coastal areas, with very harsh working conditions, such as wind sand, large temperature difference, and large salt mist. The gear and rolling bearing in the main gear box of the wind turbine share the same lubrication system, and micro-pitting surface wear easily occurs on the gear and rolling bearing, which can cause surface cracking. These tiny cracks then form micro-pits with a diameter of less than 10 microns. Under the combined action of these micro-pits, the surface cracks will continue to expand. Although these micro-pits are small, they can reduce the fit of the gear teeth, and in severe cases, can cause gear fracture failure. Therefore, improving the extreme pressure and wear resistance of the lubricating oil composition of the wind power transmission system and avoiding the occurrence of micro-pitting are important performance indicators of the lubricating oil of the wind power transmission system.
[0003] When the lubricating oil is used at high temperature, the viscosity is low, and friction and wear are easily generated. When the lubricating oil is used at low temperature, the viscosity is high, and viscous friction, even solidification, and reduced lubrication efficiency are easily generated. In order to meet the requirements of the lubricating oil for high-temperature lubricity and low-temperature fluidity, a viscosity index improver needs to be added to improve the viscosity-temperature performance of the lubricating oil product, so that the lubricating oil product has good low-temperature starting performance and high-temperature lubricating capacity, reduces fuel and lubricating oil consumption, reduces engine wear, and prolongs the service life of the lubricating oil. The viscosity index improver is an oil-soluble high molecular polymer. The viscosity index improvers on the market at present mainly include ethylene-propylene copolymer (OCP), star-shaped hydrogenated styrene isoprene copolymer (HSD), polyisobutylene (PIB), and polymethacrylate (PMA).
[0004] With the rapid development of wind power installation capacity and the increasing requirements of energy saving, environmental protection and economy in various countries, additives and oil products for improving the lubricating performance of wind power are the inevitable trend of the industry development. It is still the effort direction of those skilled in the art to develop wind power lubricating oil compositions with viscosity increasing, pour point depressing, dispersing performance, anti-wear performance and low-temperature fluidity. SUMMARY
[0005] The present application provides a lubricating oil composition and a preparation method thereof.
[0006] The lubricating oil composition of the present invention comprises: (A) a viscosity index improver; (B) a thiophenol ester type antioxidant; (C) polyisobutylene succinimide; (D) a sulfurized olefin; (E) a dialkyl dithiocarbamate and / or a dialkyl dithiocarbamate; (F) a phosphate ester; (G) a metal corrosion inhibitor; (H) a pour point depressant; and (I) a lubricating base oil; wherein the viscosity index improver is C8-C methacrylic acid. 12 Alkyl esters, C methacrylic acid 13 ~C 18 A copolymer of alkyl esters and N-vinylimidazole, in the viscosity index improver, comprising, by weight, 40% to 70% of C8-C4 methacrylic acid based on the monomer content. 12 Alkyl esters, 10%–50% (by weight) of C methacrylate 13 ~C 18 Alkyl esters, 5% to 40% (by weight) of N-vinylimidazole.
[0007] According to the present invention, the viscosity index improver contains 50% to 70% (by weight) of C8-C6 methacrylic acid, based on the number of polymerizable monomers. 12 Alkyl esters, 20%–40% (by weight) of C methacrylate 13 ~C 18 Alkyl esters, 5% to 30% (by weight) of N-vinylimidazole.
[0008] According to the present invention, the viscosity index improver has a number-average molecular weight of 2,000 to 100,000 g / mol, preferably 10,000 to 50,000 g / mol. The number-average molecular weight is determined by gel permeation chromatography (GPC) using commercially available polymethyl methacrylate standards.
[0009] According to the present invention, the method for preparing the viscosity index improver includes: reacting methacrylic acid with C8-C64... 12 Alkyl esters, C methacrylic acid 13 ~C 18 Alkyl esters, N-vinylimidazole, chain transfer agents, initiators, and solvents are mixed uniformly and copolymerized under nitrogen protection. The viscosity index improver product is then collected.
[0010] According to the present invention, the temperature of the copolymerization reaction can be 50-150°C, preferably 60-100°C; the time of the copolymerization reaction can be 2-10 hours, preferably 3-8 hours.
[0011] According to the present invention, in preparing the viscosity index improver, the methacrylic acid C8-C6 is calculated based on the polymerizable monomers. 12 Alkyl esters, C methacrylic acid 13 ~C 18The molar ratio between alkyl ester and N-vinylimidazole can be 6:1 to 8:1 to 10, preferably 3:1 to 3:1 to 4.
[0012] According to the present invention, the chain transfer agent is trithiocarbonate alkyl propionic acid, for example, 2-(dodecyltrithiocarbonate)-2-methylpropionic acid. The amount of the chain transfer agent added is C8-C6 methacrylic acid. 12 Alkyl esters, C methacrylic acid 13 ~C 18 The alkyl ester and N-vinylimidazole together account for 0.1% to 3% by weight, preferably 0.3% to 2%.
[0013] According to the present invention, the initiator may be one or more selected from azobisisobutyronitrile, benzoyl peroxide, and tert-butyl peroxide, preferably azobisisobutyronitrile; the amount of the initiator added is C8-C6 methacrylic acid. 12 Alkyl esters, C methacrylic acid 13 ~C 18 The initiator is added at a weight of 0.1% to 3%, preferably 0.2% to 2%, of the sum of the weights of the alkyl ester and N-vinylimidazole. The initiator may be added all at once or in multiple additions, such as two or three times, without particular limitation.
[0014] According to the present invention, the solvent may be one or more selected from toluene, cyclohexane, n-hexane, and petroleum ether; the amount of solvent added is C8-C6 methacrylic acid. 12 Alkyl esters, C methacrylic acid 13 ~C 18 The alkyl ester and N-vinylimidazole together account for 10% to 200% by weight, preferably 20% to 150%.
[0015] According to the present invention, after the copolymerization reaction is completed, the reaction solution can be dropwise added to a C1-C4 alcohol, the precipitate can be collected, and after drying, the viscosity index improver of the present invention can be obtained. The C1-C4 alcohol can be one or more of methanol, ethanol, propanol, and butanol, preferably ethanol. The amount of the C1-C4 alcohol can be the same as that of the C8-C4 methacrylic acid. 12 Alkyl esters, C methacrylic acid 13 ~C 18 The total mass of alkyl esters and N-vinylimidazole is 50% to 1200%.
[0016] The viscosity index improver of the present invention has excellent viscosity-temperature properties and thickening ability, as well as good pour point depressing effect, and also has good anti-wear ability and dispersing performance. It is a multifunctional viscosity index improver.
[0017] According to the present invention, the viscosity index improver accounts for 0.1% to 15% (preferably 0.5% to 10%) of the total mass of the lubricating oil composition; the thiophenol ester type antioxidant accounts for 0.01% to 10% (preferably 0.02% to 5%) of the total mass of the lubricating oil composition; the polyisobutylene succinimide accounts for 0.1% to 5% (preferably 0.2% to 3%) of the total mass of the lubricating oil composition; the sulfurized olefin accounts for 0.2% to 10% (preferably 0.5% to 8%) of the total mass of the lubricating oil composition; and the dialkyl dithiocarbamate... The acid salt and / or dialkyl dithiocarbamate account for 0.1% to 5% (preferably 0.2% to 3%) of the total mass of the lubricating oil composition; the phosphate ester accounts for 0.02% to 5% (preferably 0.1% to 3%) of the total mass of the lubricating oil composition; the metal corrosion inhibitor accounts for 0.01% to 3% (preferably 0.02% to 1%) of the total mass of the lubricating oil composition; the pour point depressant accounts for 0.02% to 5% (preferably 0.1% to 3%) of the total mass of the lubricating oil composition; and the lubricating base oil constitutes the main component of the lubricating oil composition.
[0018] According to the present invention, the thiophenol ester type antioxidant can be selected from one or more of 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dilauryl thiodipropionate and dioctadecyl thiodipropionate. Common commercial brands include IRGANOX L115 from BASF, Germany, antioxidant 1035 from Sichuan Yongye Chemical Co., Ltd., and DLTDP and DSTDP from Tianjin Lisheng Chemical Co., Ltd.
[0019] According to the present invention, the number average molecular weight of the polyisobutylene groups in the polyisobutylene succinimide can be 800-4000, preferably 900-3000, more preferably 1000-2400. Common commercial brands include T161 produced by Suzhou Special Oil Products Factory, T161A and T161B produced by Jinzhou Petrochemical Branch Additives Factory, LZL157 produced by Lubrizol Lanzhou Refinery Additives Co., Ltd., LZ6418 and LZ6420 produced by Lubrizol, and Hitec646 produced by Afton.
[0020] According to the present invention, the sulfurized olefin may be selected from isobutylene sulfide and / or diisobutylene sulfide, and common commercial brands include isobutylene sulfide T321 and diisobutylene sulfide T321D from Shenyang Guangda Chemical Co., Ltd.
[0021] According to the present invention, the dialkyl dithiocarbamate and / or dialkyl dithiocarbamate can be a mixture of dialkyl dithiocarbamate and dialkyl dithiocarbamate, and the mass ratio between the two can be 1:0.5 to 2. Common trade names include Vanlube AZ and Vanlube 7723 from Vanderbilt, and T323 from Changsha Wangcheng Additives Co., Ltd., etc.
[0022] According to the present invention, the phosphate ester can be selected from di-n-butyl phosphite and / or tricresyl phosphate. Common commercial brands include di-n-butyl phosphite T304 from Shandong Zibo Huihua Chemical Co., Ltd., tricresyl phosphate T306 from Shanghai Pengpu Chemical Plant, and Irgalube 353 from BASF in Germany.
[0023] According to the present invention, the metal corrosion inhibitor can be selected from one or more of triazole derivatives, thiazole derivatives, and thiadiazole derivatives. For example, it can be selected from one or more of benzotriazole, benzothiazole, toluenetriazole, octyltriazole, 2-mercaptobenzothiazole, 2,5-dimercapto-1,3,4-thiadiazole, 2-dimercapto-5-dithio-1,3,4-thiadiazole, and N,N-dihexylaminomethylenetriazole. Common brand names include T551, T561, and T706 from Jinzhou Kangtai Lubricating Oil Additives Co., Ltd.
[0024] According to the present invention, the pour point depressant may be selected from one or more of fumarate, vinyl acetate copolymer, polymethyl methacrylate and polyalphaolefin, and common trade names include Evonik's 1-248, 1-300 and 1-425, and Beijing Xingpu Fine Chemical Technology Development Co., Ltd.'s T866, etc.
[0025] According to the present invention, the lubricating base oil may be selected from mineral oils and / or synthetic lubricating oils. The mineral oils are generally classified into Group I, II, and III base oils, with common commercial brands including Group I 150SN and 600SN, and Group II 100N and 150N, etc. The synthetic lubricating oils include polyalphaolefins, alkylbenzenes and their derivatives, ester oils, and Fischer-Tropsch process synthetic hydrocarbon oils, with common commercial brands including PAO 4, PAO 6, PAO 8, PAO 10, and PAO 40, etc. Preferably, the lubricating base oil has a viscosity index greater than 80, a saturated hydrocarbon mass fraction greater than 90%, and a sulfur content mass fraction less than 0.03%, more preferably a mixture of Group II base oils and polyalphaolefins.
[0026] Other types of additives, such as demulsifiers and antifoaming agents, may also be added to the lubricating oil composition of the present invention, without any particular limitation.
[0027] According to the present invention, the method for preparing the lubricating oil composition includes the step of mixing the components of the aforementioned lubricating oil composition. The mixing temperature is preferably between 40°C and 90°C, and the mixing time is preferably between 1 and 6 hours.
[0028] The lubricating oil composition of the present invention has excellent extreme pressure anti-wear properties, viscosity-temperature properties, low temperature flow properties and dispersibility, and is suitable for wind power transmission systems. Detailed Implementation
[0029] The following embodiments are only used to illustrate the technical solutions of the present invention more clearly, and should not be used to limit the scope of protection of the present invention.
[0030] The main raw materials used are sourced from the following sources:
[0031] Methyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.
[0032] Isooctyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0033] Decyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0034] Dodecyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0035] Tetradecyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0036] Cetyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0037] Octadecyl methacrylate, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0038] 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0039] Azobisisobutyronitrile (AIBN), analytical grade, Beijing Innocare Technology Co., Ltd.
[0040] Ethanol, analytical grade, Beijing Innocare Technology Co., Ltd.;
[0041] Toluene, analytical grade, Beijing Innocare Technology Co., Ltd.
[0042] III4 base oil, Guangdong Maoming Petrochemical Company.
[0043] The testing method for the viscosity index improver in this invention is shown in Table 1.
[0044] Table 1
[0045]
[0046] Example 1: Preparation of viscosity index improver
[0047] To a three-necked flask equipped with an electric stirrer, add 30 mL of toluene, 17.9 g of dodecyl methacrylate, 6.22 g of tetradecyl methacrylate, 2.17 g of N-vinylimidazole, 346 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 47 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 47 mg of AIBN, and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain a terpolymer of dodecyl methacrylate, tetradecyl methacrylate, and N-vinylimidazole, which is the viscosity index improver 1 of this invention.
[0048] Example 2: Preparation of viscosity index improver
[0049] To a three-necked flask equipped with an electric stirrer, add 90 mL of toluene, 97.62 g of dodecyl methacrylate, 33.9 g of tetradecyl methacrylate, 21.2 g of N-vinylimidazole, 1107 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 165 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 165 mg of AIBN, and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 720 mL of ethanol, collect the precipitate, and dry it to obtain a terpolymer of dodecyl methacrylate, tetradecyl methacrylate, and N-vinylimidazole, which is the viscosity index improver 2 of this invention.
[0050] Example 3: Preparation of viscosity index improver
[0051] To a three-necked flask equipped with an electric stirrer, add 30 mL of toluene, 16.3 g of dodecyl methacrylate, 5.7 g of tetradecyl methacrylate, 5.2 g of N-vinylimidazole, 412 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 50 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 50 mg of AIBN, and continue stirring at 70°C for another 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain a terpolymer of dodecyl methacrylate, tetradecyl methacrylate, and N-vinylimidazole, which is the viscosity index improver 3 of this invention.
[0052] Example 4: Preparation of viscosity index improver
[0053] To a three-necked flask equipped with an electric stirrer, add 60 mL of toluene, 42.76 g of isooctyl methacrylate, 24.9 g of hexadecyl methacrylate, 8.5 g of N-vinylimidazole, 550 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 145 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 145 mg of AIBN, and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain a terpolymer of isooctyl methacrylate, hexadecyl methacrylate, and N-vinylimidazole, which is the viscosity index improver 4 of this invention.
[0054] Example 5: Preparation of viscosity index improver
[0055] To a three-necked flask equipped with an electric stirrer, add 90 mL of toluene, 61 g of decyl methacrylate, 34 g of octadecyl methacrylate, 9.4 g of N-vinylimidazole, 685 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 150 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 150 mg of AIBN, and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 400 mL of ethanol, collect the precipitate, and dry it to obtain a terpolymer of decyl methacrylate, octadecyl methacrylate, and N-vinylimidazole, which is the viscosity index improver 5 of this invention.
[0056] Comparative Example 1: Preparation of a Comparative Viscosity Index Improver
[0057] To a three-necked flask equipped with an electric stirrer, add 30 mL of toluene, 37.82 g of dodecyl methacrylate, 13.12 g of tetradecyl methacrylate, 4.88 g of methyl methacrylate, 370 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 110 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 110 mg of AIBN, and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain a terpolymer of dodecyl methacrylate, tetradecyl methacrylate, and methyl methacrylate, which is the comparative viscosity index improver 1 of this invention.
[0058] Comparative Example 2: Preparation of a viscosity index improver
[0059] To a three-necked flask equipped with an electric stirrer, add 82 mL of toluene, 61 g of decyl methacrylate, 34 g of octadecyl methacrylate, 623 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 136 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 136 mg of AIBN and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 364 mL of ethanol, collect the precipitate, and dry it to obtain a copolymer of decyl methacrylate and octadecyl methacrylate, which is the comparative viscosity index improver 2 of this invention.
[0060] Comparative Example 3: Preparation of a Comparative Viscosity Index Improver
[0061] To a three-necked flask equipped with an electric stirrer, add 30 mL of toluene, 41 g of dodecyl methacrylate, 15 g of tetradecyl methacrylate, 370 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 108 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 108 mg of AIBN and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain a copolymer of dodecyl methacrylate and tetradecyl methacrylate, which is the comparative viscosity index improver 3 of this invention.
[0062] Comparative Example 4: Preparation of a viscosity index improver
[0063] To a three-necked flask equipped with an electric stirrer, add 30 mL of toluene, 62 g of dodecyl methacrylate, 370 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 105 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 105 mg of AIBN and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain poly(dodecyl methacrylate), which is the comparative viscosity index improver 4 of this invention.
[0064] Comparative Example 5: Preparation of a viscosity index improver
[0065] To a three-necked flask equipped with an electric stirrer, add 30 mL of toluene, 69 g of tetradecyl methacrylate, 180 mg of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, and 108 mg of azobisisobutyronitrile (AIBN), and mix thoroughly. Stir at 70°C for 2 h under nitrogen protection, then add another 108 mg of AIBN and continue stirring at 70°C for 5 h to complete the reaction. Drop the reaction mixture into 240 mL of ethanol, collect the precipitate, and dry it to obtain polytetradecyl methacrylate, which is the comparative viscosity index improver 5 of this invention.
[0066] According to the test methods in Table 1, the viscosity index, thickening ability, pour point depressing performance, dispersion performance and anti-wear performance of the viscosity index improvers prepared in the examples and comparative examples were determined respectively. The test results are shown in Table 2.
[0067] As shown in Table 2, the viscosity index improver of the present invention has excellent viscosity-temperature properties and thickening ability when the molecular weight is smaller than that of the alkyl methacrylate viscosity index improver in the comparative example. This indicates that the viscosity index improver of the present invention has excellent ability to improve viscosity index and thicken, while also having good pour point depressing effect, and good anti-wear ability and dispersing performance.
[0068] Generally, the larger the molecular weight of a polymer, the stronger its thickening ability. Although the molecular weight of the viscosity index improver of this invention is smaller than that of the comparative viscosity index improver, the thickening ability of the viscosity index improver of this invention is greater than that of the comparative example, indicating that the viscosity index improver of this invention has excellent thickening ability. Simultaneously, the viscosity index of the viscosity index improver of this invention is greater than that of the comparative example, indicating that the viscosity index improver of this invention has excellent thickening ability and viscosity-temperature properties; the viscosity index improvers of comparative examples 4 and 5 have almost no pour point depressing ability, which shows that the viscosity index improver of this invention has a good pour point depressing effect, and the viscosity index improver of this invention also has good anti-wear ability and dispersing properties. Therefore, the viscosity index improver of this invention is a multifunctional viscosity index improver.
[0069] Table 2
[0070]
[0071] Examples 6-10 and Comparative Examples 6-10 of the lubricating oil compositions
[0072] According to the formulations in Table 3, lubricating oil compositions in Examples 6-10 and Comparative Examples 6-10 were prepared by stirring at 60°C for 2 hours. The II-6 base oil used had a kinematic viscosity of 6.2 mm at 100°C. 2 / s, viscosity index is 112, kinematic viscosity of PAO 40 base oil at 100℃ is 41mm. 2 / s, viscosity index is 128.
[0073] Table 3
[0074]
[0075] The kinematic viscosity, viscosity index, pour point, extreme pressure anti-wear properties, and dispersing properties of the oils in the examples and comparative examples were determined respectively. The test methods were the same as those in Table 1, and the test results are shown in Table 4.
[0076] Table 4
[0077]
Claims
1. A lubricating oil composition, comprising: (A) Viscosity index improver; (B) Thiophenol ester type antioxidant; (C) Polyisobutylene succinimide; (D) Sulfurized olefins; (E) Dialkyl dithiocarbamates and / or dialkyl dithiocarbamates; (F) Phosphate esters; (G) Metal corrosion inhibitors; (H) Pour point depressants; (I) Lubricating base oils; wherein the viscosity index improver is C8-C methacrylic acid. 12 Alkyl esters, C methacrylic acid 13 ~C 18 A copolymer of alkyl esters and N-vinylimidazole, in the viscosity index improver, comprising, by weight, 40% to 70% of C8-C4 methacrylic acid based on the monomer content. 12 Alkyl esters, 10%–50% (by weight) of C methacrylate 13 ~C 18 Alkyl esters, 5% to 40% (by weight) of N-vinylimidazole.
2. The lubricating oil composition according to claim 1, characterized in that, The viscosity index improver contains 50% to 70% (by weight) of C8-C4 methacrylic acid, based on the monomer content. 12 Alkyl esters, 20%–40% (by weight) of C methacrylate 13 ~C 18 Alkyl esters, 5% to 30% (by weight) of N-vinylimidazole.
3. The lubricating oil composition according to claim 1, characterized in that, The viscosity index improver has a number average molecular weight of 2,000 to 100,000 g / mol.
4. The lubricating oil composition according to claim 1, characterized in that, The method for preparing the viscosity index improver includes: reacting methacrylic acid (C8-C6) with C6-C6. 12 Alkyl esters, C methacrylic acid 13 ~C 18 Alkyl esters, N-vinylimidazole, chain transfer agents, initiators, and solvents are mixed uniformly and copolymerized under nitrogen protection. The viscosity index improver product is then collected.
5. The lubricating oil composition according to claim 4, characterized in that, The copolymerization reaction is carried out at a temperature of 50–150°C (preferably 60–100°C) and for a duration of 2–10 h (preferably 3–8 h).
6. The lubricating oil composition according to claim 4, characterized in that, In preparing the viscosity index improver, based on the polymer monomer, the methacrylic acid C8-C9... 12 Alkyl esters, C methacrylic acid 13 ~C 18 The molar ratio between alkyl ester and N-vinylimidazole is 6:1 to 8:1 to 10 (preferably 3:1 to 3:1 to 4).
7. The lubricating oil composition according to claim 4, characterized in that, The chain transfer agent is trithiocarbonate alkylpropionic acid; and / or, the initiator is selected from one or more of azobisisobutyronitrile, benzoyl peroxide and tert-butyl peroxide; and / or, the solvent is one or more of toluene, cyclohexane, n-hexane and petroleum ether.
8. The lubricating oil composition according to claim 4, characterized in that, After the copolymerization reaction is complete, the reaction solution is added dropwise to a C1-C4 alcohol, the precipitate is collected, and after drying, the viscosity index improver is obtained.
9. The lubricating oil composition according to any one of claims 1 to 8, characterized in that, The viscosity index improver comprises 0.1% to 15% (preferably 0.5% to 10%) of the total mass of the lubricating oil composition; the thiophenol ester type antioxidant comprises 0.01% to 10% (preferably 0.02% to 5%) of the total mass of the lubricating oil composition; the polyisobutylene succinimide comprises 0.1% to 5% (preferably 0.2% to 3%) of the total mass of the lubricating oil composition; the sulfurized olefin comprises 0.2% to 10% (preferably 0.5% to 8%) of the total mass of the lubricating oil composition; and the dialkyl dithiocarbamate and / Or the dialkyl dithiocarbamate accounts for 0.1% to 5% (preferably 0.2% to 3%) of the total mass of the lubricating oil composition; the phosphate ester accounts for 0.02% to 5% (preferably 0.1% to 3%) of the total mass of the lubricating oil composition; the metal corrosion inhibitor accounts for 0.01% to 3% (preferably 0.02% to 1%) of the total mass of the lubricating oil composition; the pour point depressant accounts for 0.02% to 5% (preferably 0.1% to 3%) of the total mass of the lubricating oil composition; and the lubricating base oil constitutes the main component of the lubricating oil composition.
10. The lubricating oil composition according to any one of claims 1 to 8, characterized in that, The thiophenol ester type antioxidant is selected from one or more of 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dilauryl thiodipropionate, and dioctadecyl thiodipropionate; the number average molecular weight of the polyisobutylene group in the polyisobutylene succinimide is 800-4000; the sulfurized olefin is selected from sulfurized isobutylene and / or sulfurized diisobutylene; the dialkyl dithiocarbamate and / or dialkyl dithiocarbamate are selected from dialkyl di... The mixture comprises thiocarbamate and dialkyl dithiocarbamate in a mass ratio of 1:0.5 to 2; the phosphate ester is selected from di-n-butyl phosphite and / or tricresyl phosphate; the metal corrosion inhibitor is selected from one or more of triazole derivatives, thiazole derivatives and thiadiazole derivatives; the pour point depressant is selected from one or more of fumarate, vinyl acetate copolymer, polymethyl methacrylate and polyalphaolefin; and the lubricating base oil is selected from mineral oil and / or synthetic lubricating oil.
11. A method for preparing a lubricating oil composition according to any one of claims 1 to 10, comprising the step of mixing the components therein.